PRIMER-PRIMER BARU UNTUK MENGAMPLIFIKASI GEN PENGKODE PROTEIN AMPLOP VIRUS DENGUE STRAIN CH53489 - Ira Djajanegara (BERITA BIOLOGI, 2010)
Restriction site of BamHI and Sail must be added in order to express the gene encoding envelope protein of dengue virus strain CH53489 (gene E) into expression vector pMAL-p2x. This approach required the PCR technique for amplification as well as restriction sites addition. However, PCR amplification is prone to error due to the process of misincorporation eventhough using Platinum taq polymerase. Therefore, it is important to be concern that there will be no alteration of the gene especially for biopharmaceutical purposes such as recombinant vaccine. This experiment was aimed to design several primers of DenV-M F, D3-1715s, D3-2117s, D3-1911c and DenV-M R for full length sequencing of the amplified products. Primers were designed in silico using Oligo Explorer and tried in vitro to check the ability of the primers to produce fragments. The sequencing results showed that the amplified product suffered from misincorporation during amplification (98.9% homology). However, the 3-D protein structure prediction did not show any major changes in the protein structure. Further analysis of the expressed protein is required to be used for biopharmaceutical purposes.